Autophagy inhibition in intestinal stem cells favors enteroendocrine cell differentiation through Stat92E activity. - Lacarrière-Keïta, C.; Nassari, S.; Boutet, J.; Gaudreault, V.; Jean, S. (Disease models & mechanisms, 2025)
Because the intestinal epithelium is exposed to various stressors, dysregulation of essential mechanisms that maintain gut homeostasis, such as autophagy, has been linked to inflammatory bowel pathologies. In Drosophila melanogaster, inhibition of autophagy specifically in adult intestinal stem cells (ISCs) affects their proportions differently during aging. Proper intestinal renewal requires a balance between ISC proliferation and differentiation. Here, we showed that, in adult ISCs, loss of core autophagy genes and regulators of autophagosome-lysosome fusion increases the enteroendocrine cell population and enhances the transcriptional activity of Stat92E. Functional experiments involving cell fate regulators of enteroendocrine or enterocyte differentiation and proliferation suggested that dysfunctional autophagy in adult ISCs enhances Stat92E activity downstream of Hop/JAK kinase. Finally, lineage-tracing analyses confirmed that autophagy inhibition promotes enteroendocrine cell differentiation. Thus, our data demonstrate that, under homeostatic conditions, basal autophagy limits enteroendocrine cell differentiation by regulating Stat92E activity, which can be counteracted by the transcription factor Scute.